PERAN GURU DALAM MENSTIMULUS KECERDASAN MAJEMUK ANAK USIA DINI DI LINGKUNGAN - Raya Idul Fitri; Inayatu Safitri; Annisa Zakhra Manullang; Zuhrona Siregar; Ade Nurcahyani Ritonga; Fauziah Nasution (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to explore the role of early childhood educators in stimulating multiple intelligences in young children within the school environment, responding to the growing importance of holistic and personalized approaches during the golden age of development. Employing a qualitative case study design, the research was conducted in an early childhood education institution in Indonesia. Data were collected through in-depth interviews with five early childhood teachers, direct classroom observations, and analysis of daily lesson plans. Thematic analysis revealed that teachers play a central role in identifying and nurturing various forms of intelligence, including linguistic, logical-mathematical, musical, bodily-kinesthetic, spatial, interpersonal, intrapersonal, and naturalistic intelligences. Teachers utilized thematic instruction, differentiated activities, and created rich learning environments to stimulate diverse intelligences. Additionally, teacher sensitivity to children’s unique characteristics and reflective teaching practices significantly enhanced the effectiveness of stimulation strategies. This study contributes to the existing literature on the application of Multiple Intelligences theory in early childhood education and underscores the need for professional development programs that equip teachers to design responsive learning experiences. Practical implications include the need for policy support to improve early childhood educators’ pedagogical competencies. Further research involving a larger and more culturally diverse sample is recommended to broaden the generalizability of findings.